Impact of metal ion’s charge on the interatomic Coulombic decay widths in microsolvated clusters - Stumpf, Vasili; Brunken, Christoph; Gokhberg, Kirill (The journal of chemical physics, 2016)
Interatomic Coulombic decay (ICD) is an efficient electronic decay mechanism of electronically excited atoms and molecules embedded in an environment. For the series of isoelectronic Na+, Mg2+, and Al3+ ions in aqueous solution, ultrashort ICD lifetimes of 3.1 fs, 1.5 fs, and 0.9 fs, respectively, were observed experimentally. The magnitude of the ICD lifetimes and their variation within the series were qualitatively explained by shortening metal-oxygen equilibrium distances and the increasing polarization of the water molecules as the metal’s charge grows. We carried out an extensive ab initio investigation of the variation of the ICD widths with the metal-oxygen distances and the number of water neighbors in Na+-(H2O)m (m = 1-4) and Mg2+-(H2O)n (n = 1-6) clusters including and excluding polarization effects in the decaying state. We demonstrated that the effect of the induced polarization of the water ligand and the equilibrium cation-oxygen distance are equally important in determining the ordering and ratios of the ICD lifetimes in the series. Moreover, we showed that the induced polarization of the water molecules leads to a slower than linear growth of ICD width with the number of equivalent water neighbors; the non-linearity is stronger for Mg2+. The ab initio ICD widths in microsolvated Na+-(H2O)4 and Mg2+-(H2O)6 clusters are found to be in good agreement with the experimental values.